2009
DOI: 10.1016/j.neuropsychologia.2009.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Are impairments in visual-spatial attention a critical factor for increased falls risk in seniors? An event-related potential study

Abstract: Falls are experienced annually by approximately one third of community dwellers over the age of 65, and while neuro-cognitive deficits have been shown to increase falls risk, the specific nature of these deficits remain unspecified. Here we examined whether visual-spatial attention may be a core neuro-cognitive system showing abnormal function in fallers. Using a between-groups design, we recorded event-related potentials in a canonical spatial cuing task performed by two groups of senior (aged 65+ years old) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…Our primary result regarding the relationship between falls risk and attentional facilitation corroborates and extends our previous finding that older adults with a history of falls have altered visual-spatial attention to the left hemifield (Nagamatsu et al, 2009). Based on the notion that the right hemisphere is exclusively responsible for orienting attention to the left side of visual space (e.g., Mangun et al, 1994), this pattern of results is consistent with what is observed in patients with left visual neglect following right hemisphere damage (e.g., Bublak, Redel, & Finke, 2006;Reuter-Lorenz, Kinsbourne, & Moscovitch, 1990).…”
Section: Primary Findingsupporting
confidence: 90%
See 3 more Smart Citations
“…Our primary result regarding the relationship between falls risk and attentional facilitation corroborates and extends our previous finding that older adults with a history of falls have altered visual-spatial attention to the left hemifield (Nagamatsu et al, 2009). Based on the notion that the right hemisphere is exclusively responsible for orienting attention to the left side of visual space (e.g., Mangun et al, 1994), this pattern of results is consistent with what is observed in patients with left visual neglect following right hemisphere damage (e.g., Bublak, Redel, & Finke, 2006;Reuter-Lorenz, Kinsbourne, & Moscovitch, 1990).…”
Section: Primary Findingsupporting
confidence: 90%
“…We previously found that older adults with a history of falls exhibited reduced attentional facilitation during an orienting task -but that this effect was specific to the left visual field (Nagamatsu et al, 2009). Given the contralateral nature of visual processing, impaired visual-spatial attention exclusively on the left side of visual space is indicative of problems with function and/or structure of the right hemisphere.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, while we did not anticipate reaction times to be associated with falls (e.g., Nagamatsu et al, 2009), we did hypothesize that falls would be associated with task accuracy -or errors of commission -based on the idea that older adults with a history of falls have poorer response inhibition (Liu-Ambrose et al, 2008; Liu-Ambrose, Katarynych, Ashe, Nagamatsu, & Hsu, 2009;Lord & Fitzpatrick, 2001;McGough et al, 2011).…”
mentioning
confidence: 94%